Sistem Informasi Manajemen Perguruan Tinggi Dalam Bidang Pendataan Pendidikan Tinggi - Bambang S Joko (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2010)
The purpose of descriptive research is to determine the objective conditions of the problems and constraints, data collection mechanisms, and use of information and communication technology to support higher education management information system. The approach used is kunatitatif approach that leads to the observation or measurement data expressed in numbers to get a picture of the problems faced by PT. This sample includes 30 countries and 30 private universities from 30 provinces in Indonesia. Please note, there are currently 83 government-run public universities, private universities and 2598 are managed by the private sector. With stratified random sampling method. PT PT grouped by type, then from each PT group took some samples to represent the 30 provinces. In qualitative data analysis techniques, namely descriptive measures argumentative with data description, data analysis, and conclusions. Study results showed that the majority of PT has conducted data collection and processing on a regular basis every year. Documenting all this walking is still dominated by the instrument of data collection via questionnaires, either by the Directorate General of Higher Education and Ministry of Education Research and Development Center for Education Statistics. There are two main causes of delay in data collection, the first coming from the government (Directorate General of Higher Education Department of Education and Research and Development PSP), and the second coming of PTâ€™s own institution. Not to mention, there were respondents who felt not received a census questionnaire. The dominant constraints in SIM management of PT is a problem of human resources, and yet all the PT who become SIM PT sample of this study, and nearly half of the respondents complained that some of the applications used for SIM PT they are still not operating correctly.Â ABSTRAKÂ Tujuan studi deskriptif ini adalah untuk mengetahui berbagai permasalahan dan hambatan, mekanisme pendataan, serta pemanfaatan teknologi informasi dan komunikasi (TIK) dalam mendukung sistem informasi manajemen perguruan tinggi. Pendekatan yang dilakukan adalah pendekatan kuantitatif melalui observasi atau pengukuran data untuk mendapatkan gambaran permasalahan yang dihadapi PT. Sampel studi terdiri atas 30 PTN dan 30 PTS dari 30 provinsi di Indonesia yang dipilih secara stratified random sampling. Teknik analisis data dilakukan secara kualitatif, yakni secara deskriptif argumentatif dengan langkah-langkah pendeskripsian data, analisis data, dan penyimpulan. Hasil studi menunjukkan bahwa sebagian PT telah melaksanakan pengumpulan dan pengolahan data secara rutin setiap tahun. Pendataan didominasi oleh pengumpulan data melalui instrumen kuesioner, baik oleh Ditjen Dikti maupun oleh PSP Balitbang Depdiknas. Dua penyebab utama terhambatnya pendataan dari Ditjen Dikti dan PSP Balitbang Depdiknas dan dari institusi PT itu sendiri. SDM merupakan hambatan yang dominan dalam pengelolaan SIM PT dan belum semua PT yang menjadi sampel studi memiliki SIM PT, dan hampir separuh responden menunjukkan bahwa belum semua aplikasi SIM PT beroperasi dengan baik.